The SPEECH ACT ANALYSIS REFLECTED ON FEMALE DIGITAL COMIC MAKERS OF UIN RADEN MAS SAID SURAKARTA - winarti winarti; Aris Hidayatulloh (Proceeding of International Conference on Science, Health, And Technology, 2022)
This study discusses speech acts in the Digital Comics discourse made by UIN Raden Mas Said Surakarta students who are members of the Creative Digital Skills Development Class. The comic discourse campaigns for the importance of tolerance from both religion and fellow human beings. The digital comics were created in a creative digital skills class held by the English Literature study program at UIN Raden Mas Said Surakarta. Through digital comic discourse, female students create their ideas with the theme of tolerance. By using Searle’s theory, speech act analysis in the discourse is carried out. Searle gave further categories of illocutionary speech acts into representative, directive, commissive, expressive, and declarative categories. These categories make it easier for researchers to see specifically the intended meaning. The data from this study emphasize the utterances spoken by the main characters of the comics. In addition, images from the data become secondary data from this study because the discourse consists of two units, namely text (verbal) and images (non-verbal). The data is processed and classified into several speech act classifications proposed by Searle. The data is described by the qualitative method. The results of this study indicate that speech acts reflected from digital comics by students of UIN Raden Mas Said Surakarta have topics that refer to tolerance and maintaining harmony between religions or friends. In this work, students took three main sub-themes, namely 1) inter-religious harmony, 2) harmony among friends, and 3) harmony among neighbors. Character emphasizes the female character. The stories of the characters also affect the storyline, most of which emphasize caring and caring for each other, especially for women of different religions or different backgrounds. In terms of speech acts, from the 15 data collected, there are Directive, Expressive, and Representative with the directive portion being more dominant. The results show that 46.2 percent of the main characters show directive speech acts. Expressive speech acts show the second dominant speech act with a percentage of 33 percent. While the representative 13.2 percent in representative speech acts. While the declarative percentage shows 6.6 percent. From this percentage, it can be concluded that the use of directive speech acts is the main and most effective reference in conveying the moral message of an invitation, namely an invitation to maintain harmony. While expressive speech acts are used as speech acts that reflect empathy for others. In this case empathy between friends or religion.